SHORT-TERM FORECAST FOR THE GROWTH OF INDONESIA'S NEW RENEWABLE ENERGY USING THE ADAPTIVE NEURO-FUZZY INFERENCE SYSTEM - Ginting, Riski Titian; Tri Nugraha, Yoga; Perangin-Angin, Despaleri; Gultom, Togar Timoteus; Nainggolan, Winner Parluhutan; Sitanggang, Delima (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Electric power plants always use fossil fuels such as coal, oil, etc. However, the fossil fuel supply in Indonesia is decreasing from year to year. This causes power plants to be powered by using fuels that will not run out, such as solar Energy, water, wind, and others. Solar Energy, water, wind, and others are Alternative Energy or can also be called New and Renewable Energy. To guarantee a power plant powered by alternative Energy, it must be analyzed regarding the growth of new and renewable Energy. The method used in analyzing the development of new and renewable Energy is the Adaptive Neuro Fuzzy Inference System Method. MW or 0.599%. This result has increased yearly in Indonesia's new and renewable energy growth.